The Remoteness of Remote Learning: A Policy Lesson from COVID19 - Eder, Rosalyn (Journal of Interdisciplinary Studies in Education, 2020)
The measures enforced by governments to contain the highly contagious COVID19 pathogen laid bare the deep inequalities that beset education systems around the world. The lockdowns and subsequent closures of educational institutions have amplified the gap between the rich and the poor, not just between the Global North and the Global South, but within countries as well. As of April 6th, UNESCO reported that 188 countries have temporarily closed its educational institutions, while several countries implemented localized closures, affecting 1,576,021,818 learners. Accordingly, education authorities have urged for classes at all levels to be moved online, a sudden but necessary emergency response to COVID19. However, for disadvantaged groups, the problem is how to meet the basic conditions that remote learning requires.